The Effect of Infant Massage Therapy on Premature Infant Weight Gain - Novryanti, Suci (Jurnal Health Society, 2024)
Introduction: Premature babies are babies born before 37 weeks of gestation. Generally, premature babies in Indonesia weigh less than they should. One aspect that is believed to increase the weight of premature babies is baby massage therapy. The purpose of this study was to determine the effect of infant massage therapy on the weight gain of premature babies in the Markisa room at Sayang Cianjur Hospital Method: Type of correlational research with One group pre-test and post-test designe. The population was babies born prematurely in the Markisa Room at Sayang Cianjur Hospital with a sample of 18 people. Sampling using purposive sampling. Research instruments are tools used for data collection. Data collection used baby massage SOP, baby massage equipment, and baby weight scales and check list sheets. And statistical analysis using paired sample t-test. Result: The results showed that there was an effect of baby massage therapy on the weight gain of premature babies in the Markisa room with a p-value of 0.000 (<0.05). Conclusion: There is an effect of infant massage therapy on the weight gain of premature infants in the Markisa room.